Pembelajaran PPKn di Sekolah Dasar sebagai Sarana Penanaman Nilai Pancasila, Nasionalisme, dan Tanggung Jawab Warga Negara - Asysyfa Marsidino; Ignatia Putri Malika; Shafa Kaylana Azizah; Aulia Agustina (Universitas PGRI Madiun, 2026)
This research aims to analyze the contribution of Pancasila and Civic Education (PPKn) at the elementary school level in internalizing Pancasila values, strengthening nationalistic commitment, and constructing students' accountability. The methodological approach applied is a literature review through a descriptive qualitative design, utilizing secondary data from reputable scientific articles published between 2020 and 2025, which were analyzed using content analysis techniques. The research findings confirm that civic instruction plays a crucial role in students' moral reconstruction by instilling ideological principles, patriotism, and personal responsibility. The efficacy of these learning outcomes heavily relies on the integration of active and contextual pedagogical strategies, although practical implementation is still hindered by challenges such as the hegemony of conventional expository methods, a shortage of interactive media, and a lack of synergistic partnership between educational institutions and the family ecosystem. Therefore, the implementation of innovative reforms in civic education is an absolute prerequisite to optimize the holistic acceleration of student character building.